The division of ownership in new ventures - Dominique M. Demougin; Oliver Fabel (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
The current study investigates a tripartite incentive contract between an innovator supplying an intellectual asset, a professional assigned to productive tasks, and a consulting firm specializing in matching ideas and professional skills. A rather simple pure tripartite partnership implements the consultant's expected profit maximum and maximizes the project's expected surplus. The liquidity-constrained professional is compensated by receiving a share of one half in the new venture. The consultant's and the innovator's shares reflect the relative value of search. However, the consultant's optimal search effort to find an appropriate production partner is inefficiently low.
Keywords: M13; M21; 330; new ventures; tripartite incentive contract; consulting contract; partnerships; Theorie der Unternehmung; Anreizvertrag; Unternehmensgründung